Observation and Ultrafast Dynamics of Inter‐Sub‐Band Transition in InAs Twinning Superlattice Nanowires. Issue 40 (2nd September 2020) - Xue, Mengfei; Li, Ming; Huang, Yisheng; Chen, Runkun; Li, Yunliang; Wang, Jingyun; Xing, Yingjie; Chen, Jianjun; Yan, Hugen; Xu, Hongqi; Chen, Jianing
Abstract: A variety of infrared applications rely on semiconductor superlattices, including, notably, the realization of high‐power, compact quantum cascade lasers. Requirements for atomically smooth interface and limited lattice matching options set high technical standards for fabricating applicable heterostructure devices. The semiconductor twinning superlattice (TSL) forms in a single compound with periodically spaced twin boundaries and sharp interface junctions and can be grown with convenient synthesis methods. Therefore, employing semiconductor TSL may facilitate the development of optoelectronic applications related to superlattice structures. Here, it is shown that InAs TSL nanowires generate inter‐sub‐band transition channels due to the band projection and the Bragg‐like electron reflection. The findings reveal the physical mechanisms of inter‐sub‐band transitions in TSL structure and suggest that TSL structures are promising candidates for mid‐infrared optoelectronic applications. Abstract : The periodically spaced twin boundaries in semiconductors may introduce an extraordinary miniband structure and lead to mid‐infrared inter‐sub‐band transitions. Near‐field infrared nano spectroscopy is employed to reveal this subtle but substantial mid‐infrared transition in twin boundaries of well‐engineered InAs twinning superlattice nanowires. Near‐field pump–probe measurements demonstrate the rich details of the mid‐infrared transition dynamics.